2012
DOI: 10.1159/000341754
|View full text |Cite
|
Sign up to set email alerts
|

High-Flow Nasal Cannulae for Respiratory Support of Preterm Infants: A Review of the Evidence

Abstract: Background: High-flow nasal cannulae (HFNC) are gaining in popularity as a form of non-invasive respiratory support for preterm infants in neonatal intensive care units around the world. They are proposed as an alternative to nasal continuous positive airway pressure (NCPAP) in a variety of clinical situations, including post-extubation support, primary therapy from birth and ‘weaning’ from NCPAP. Objectives: To present and discuss the available evidence for the use of HFNC in the preterm population. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 64 publications
0
78
2
1
Order By: Relevance
“…However, large randomized trials have not been performed comparing efficacy of HFNC with that of nasal CPAP. 19 Because methods of weaning CPAP vary in clinical practice, several studies have evaluated alternative CPAP weaning protocols. [24][25][26][27] In a multi-center, randomized control trial comparing 3 CPAP weaning protocols, Todd et al 24 demonstrated that decreasing CPAP pressure rather than cycling time off CPAP is the most effective method for CPAP weaning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, large randomized trials have not been performed comparing efficacy of HFNC with that of nasal CPAP. 19 Because methods of weaning CPAP vary in clinical practice, several studies have evaluated alternative CPAP weaning protocols. [24][25][26][27] In a multi-center, randomized control trial comparing 3 CPAP weaning protocols, Todd et al 24 demonstrated that decreasing CPAP pressure rather than cycling time off CPAP is the most effective method for CPAP weaning.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17] To reduce lung injury from mechanical ventilation, noninvasive modes of respiratory support, such as nasal CPAP and high-flow nasal cannula (HFNC), have been increasingly used. [18][19][20][21][22][23] However, there is no agreement on best practices for weaning these devices. [24][25][26][27] Noninvasive in-dicators demonstrating readiness for reducing respiratory support are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Several clinical trials over the last decade have collected evidence of the use of HHHFNC in preterm infants, both as a primary mode of support at birth and after extubation from MV. We conducted a systematic review and metaanalysis to collect all published information, to be able to guide clinical practice.…”
mentioning
confidence: 99%
“…L'evidenza dell'efficacia della HFNC nelle patologie respiratorie neonatali comunemente gestite con la NCPAP è tuttavia ancora limitata. 13 Benché l'utilizzo della terapia con HFNC si stia diffondendo nei reparti di terapia intensiva neonatale, solo un numero limitato di studi, per lo più osservazionali, è stato pubblicato in relazione al suo utilizzo nella gestione delle patologie respiratorie del neonato, in particolare del prematuro con distress respiratorio (14). Tali studi risultano, peraltro, molto eterogenei per caratteristiche demografiche e cliniche dei pazienti studiati, materiali e metodi utilizzati, obiettivi primari e secondari.…”
Section: Discussioneunclassified